Effect of hydroxypropyl methylcellulose on physicochemical characteristics of high protein jasmine rice coated with rice protein isolate - Chanikan Sonklin; Nachomkamon Saengsuk; Parnpailin Wiyaporn; Prapawadee Yodlum; Putthapong Phumsombat (LWT, 2026)
This study investigated the effects of hydroxypropyl methylcellulose (HPMC; 0, 2.5, 5, and 10 g/L) on the physicochemical properties of coated high-protein jasmine rice. Water holding capacity (WHC), texture, color, protein content, zeta potential, Fourier transform infrared (FTIR) spectroscopy, microstructure, and differential scanning calorimetry (DSC) were evaluated to identify optimal coating performance. Moderate HPMC concentrations (2.5–5 g/L) significantly improved WHC and produced the softest and least adhesive cooked rice, consistent with a porous and open microstructure observed by SEM. The highest protein content was obtained at 5 g/L HPMC, indicating improved coating uniformity and film cohesion. Increasing HPMC concentration resulted in more negative zeta potential values, suggesting enhanced dispersion stability. FTIR analysis revealed strengthened O–H and carbohydrate-associated bands at moderate HPMC levels, indicating enhanced hydrogen bonding and polysaccharide deposition. DSC results showed that all coated samples exhibited lower retrogradation enthalpy than the control, with the lowest structural ordering observed at 2.5–5 g/L HPMC. Excessive HPMC (10 g/L) formed a denser matrix, partially increasing hardness and enthalpy without exceeding the control. Overall, moderate HPMC concentrations effectively optimized hydration behavior, texture, and coating stability of high-protein jasmine rice. • A hydrocolloid-assisted edible coating was developed to produce high-protein jasmine rice • Moderate HPMC levels (2.5–5 g/L) improved texture, hydration, and protein deposition • Excessive HPMC increased matrix densification and partially restored starch retrogradation • FTIR, SEM, and DSC revealed concentration-dependent starch–hydrocolloid interactions • HPMC enhanced coating stability and reduced phase separation in protein-rich dispersions
Keywords: Food composition and properties; Nanocomposite Films for Food Packaging; Proteins in Food Systems